THE INFLUENCE OF RELATIONAL MARKETING AND LOYALTY ON CUSTOMER SATISFACTION PT. BANK SUMUT (BPDSU) MEDAN - Rifky Budi Setiawan (Sean Institute, 2023)
PT. Bank Sumut established since 1961, Customer satisfaction can be created through marketing quality provided by the company to its customers. The better the quality of its services, the higher the customer loyalty to the company that will create customer satisfaction by itself. Hypothesis Test Results rational marketing variables (X1) on customer satisfaction at the results obtained relational marketing job characteristics (X1) partially have a significant influence on customer satisfaction (Y) PT. Bank Sumut (Persero) Tbk Medan Branch. obtained t value of 3.937 with a probability value t (Sig) is 0.000 (Sig. <α0.05). Hypothesis Test Results loyalty variables on customer satisfaction in the results obtained Loyalty variable (X2) partially has a significant influence on customer satisfaction (Y) PT. Bank Sumut (Persero) Tbk Medan Branch. It can be concluded that the relationship marketing (X1) and loyalty (X2) simultaneously have a significant influence on customer satisfaction (Y) PT Bank Sumut Tbk.